2019
DOI: 10.18510/hssr.2019.7696
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Healthcare System in Indonesia in 2014-2018

Abstract: Purpose of the study: The purpose of the study is to measure the efficiency of the healthcare system in Indonesia in 2014-2018. Methodology:The Data Envelopment Analysis model was used to analyze 33 Provinces in Indonesia in the 2014-2018 period. The input variables are the number of health human resources at the community health centre, health human resources at the hospital, the number of hospitals, the number of community health centres and the realization of per capita deconcentration health funds. The out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(24 reference statements)
0
3
0
3
Order By: Relevance
“…(Mulyanto, Kunst, and Kringos 2019). Another study in the same period stated that the majority of regions with efficient health care systems in Indonesia in 2018 were on the island of Java (Atmanti and Naylah 2019) Most studies have focused on the distribution of the health workforce and resources as the key factor in the disparities in utilisation of health services., such as the unequal distribution of budget, personnel, and facilities (Hosseinpoor, Bergen, and Floranita 2017). The disparity in the distribution of health workers as reflected in the results of this study is also in line with previous studies which showed that public primary care in Eastern Indonesia experienced more vacancies, especially doctors and midwives, so that the coverage of primary health services that were oriented to promotive and preventive tended to be neglected (Hikmah, Rahman, and Puspitasari 2020).…”
Section: District/city Primary Health Service Efficiency Level In Ind...mentioning
confidence: 99%
“…(Mulyanto, Kunst, and Kringos 2019). Another study in the same period stated that the majority of regions with efficient health care systems in Indonesia in 2018 were on the island of Java (Atmanti and Naylah 2019) Most studies have focused on the distribution of the health workforce and resources as the key factor in the disparities in utilisation of health services., such as the unequal distribution of budget, personnel, and facilities (Hosseinpoor, Bergen, and Floranita 2017). The disparity in the distribution of health workers as reflected in the results of this study is also in line with previous studies which showed that public primary care in Eastern Indonesia experienced more vacancies, especially doctors and midwives, so that the coverage of primary health services that were oriented to promotive and preventive tended to be neglected (Hikmah, Rahman, and Puspitasari 2020).…”
Section: District/city Primary Health Service Efficiency Level In Ind...mentioning
confidence: 99%
“…23 Based on the rights and obligations of the patient, the legal relationship between the patient and the doctor in health services will bring legal impact. 24 The impact of this law can be regarding the legal responsibilities of doctors to patients in case of violations of law, ethics and discipline. 25…”
Section: Patientmentioning
confidence: 99%
“…Fasilitas kesehatan ini termasuk ketersediaan rumah sakit, pusat kesehatan masyarakat (puskesmas), sumber daya kesehatan di pusat kesehatan masyarakat dan di rumah sakit, dan ketersediaan pengeluaran kesehatan. Dalam penelitian ini, akan menggunakan teknik DEA untuk mengevaluasi teknik efisiensi dari pelayanan kesehatan (Atmanti, 2019).…”
Section: Tinjauan Pustakaunclassified
“…Penelitian ini menggunakan data sekunder yang diambil dari BPS dan Kementerian Kesehatan pada tahun 2016-2018. Penentuan input dan output yang diambil pada penelitian ini mengacu kepada jurnal The Efficiency of Healthcare System in Indonesia in 2014-2018 (Atmanti & Naylah, 2019). Akan tetap, penggunaan input dan output untuk perhitungan efisiensi pada penelitian ini terbatas hanya memakai input berupa rasio dokter umum puskesmas per 100.000 penduduk, rasio perawat per 100.000 penduduk, rasio RS umum dan khusus per 100.000 penduduk dan rasio Puskesmas per 100.000 penduduk.…”
Section: Metode Penelitianunclassified